Obedience to Constitutional Court Decisions: Constitutional Obligations and Moral Obligations of Legislators - Mujiyana, Mujiyana; Virdinia Putri, Windy; Fuadi, Gumilang (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2025)
It is stated in the constitution that the Constitutional Court is the court of first and last instance whose decision is final. Problems arise when the Constitutional Court's decision requires follow-up to make it happen and other institutions follow up on it. This research is normative research that examines compliance with the Constitutional Court's decision as a constitutional obligation to legislate and a moral obligation to legislate using a conceptual approach. The results of this research show that non-compliance with the Constitutional Court's decision is a form of disloyalty and defiance of the constitution itself or what is referred to as constitutional disobedience. In addition, with the consideration that the Constitutional Court is a negative legislature, there are no special enforcement agencies, and there are no juridical consequences for ignoring the Constitutional Court's decision. Thus, the application of Lawrence Kohlberg's 4 moral orientations must be put forward as fulfilling moral obligations. This research concluded that obedience to the Constitutional Court decisions is not only a constitutional obligation for legislators but also a moral obligation for legislators.